If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -30 = 0 Reorder the terms: -30 + x = 0 Solving -30 + x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '30' to each side of the equation. -30 + 30 + x = 0 + 30 Combine like terms: -30 + 30 = 0 0 + x = 0 + 30 x = 0 + 30 Combine like terms: 0 + 30 = 30 x = 30 Simplifying x = 30
| (14/3)/(7/5) | | x^2+4x-x-4= | | 39=19+10p | | (29/4)/(5/6) | | (15/2)/(21/8) | | 1/c+1/d/c+d | | -98=-12y-2 | | 68=1/2(11)(x) | | 15/2/21/8 | | 6k+(-8k)= | | (3x-5)(4x^4-3x^3+2x^2-x+1)= | | 5=y-10 | | 7z-9=-9 | | 5+1/4y=6 | | 5x^2-17+6=0 | | 1/4y=10 | | (5x^2+2x-3)-(7x^3-4x^2+2)= | | 5n-10=n+50 | | 16x^3y-54y= | | x^2-24x+144+256=x^2 | | 5y-15x=45 | | 14x+55=11x+94 | | 7x-4(x-3)=33 | | t/250=150/375 | | 1/4(2x+5)=x-2/5 | | =(7x+9y-2x)(8x-3x-3y) | | 7x+1=2x+6 | | 1/2+(0.7)2 | | (3x+2)=(x-7) | | -9x+63=135 | | (m^-1m5/m^-2)^-3 | | -1/12x+8=7/6 |